Modernized Digital Marketing Strategies to Improve Customer Experience and Engagement - Trupti Dandekar Humnekar, Narendar Chinthamu, Koneti Chaitanya, Srivarun Venkatesh, Avinash Kumar Mishra, Sneha Soni (European Economic Letters (EEL), 2024)
The revolutionary power of contemporary digital marketing methods on improving customer experience and engagement is examined in this research. Businesses must use creative strategies in today's quickly changing digital environment if they want to engage their target audience. Organizations can customize their marketing efforts to cater to the unique requirements and inclinations of individual clients by utilizing sophisticated tools and strategies like artificial intelligence, data analytics, and tailored content distribution. This study looks at the essential elements of contemporary digital marketing tactics and how they affect consumer perceptions, contentment, and brand loyalty. It clarifies the useful uses and advantages of using these tactics to create a sustainable competitive edge in the digital age through case studies and industry insights. Businesses must employ clever digital marketing strategies to improve client experiences and increase consumer involvement if they want to stay ahead of the competition and expand in this digital age. This study examines how customer happiness and relationships have evolved in digital marketing to highlight how critical it is to boost customer satisfaction. This work involved extensive evaluation and investigation. It examines emerging trends such as interactive content, tailored marketing, and the application of cutting-edge technologies like artificial intelligence (AI) and augmented reality (AR). The primary goal of the study is to determine the relationship between engagement metrics and marketing success by examining how digital marketing influences consumer satisfaction and loyalty.